Novel Species Interactions in a Highly Modified Estuary: Association of Largemouth Bass with Brazilian Waterweed Egeria densa. Issue 2 (26th February 2016) - Conrad, J. Louise; Bibian, Andrew J.; Weinersmith, Kelly L.; De Carion, Denise; Young, Matthew J.; Crain, Patrick; Hestir, Erin L.; Santos, Maria J.; Sih, Andrew
Abstract: Frequent invasions in coastal ecosystems result in novel species interactions that have unknown ecological consequences. Largemouth Bass Micropterus salmoides and Brazilian waterweed Egeria densa are introduced species in the Sacramento–San Joaquin River Delta (the Delta) of California, a highly modified estuary. In this system, Brazilian waterweed and Largemouth Bass have seen marked increases in distribution and abundance in recent decades, but their association has not been specifically studied until now. We conducted a 2‐year, bimonthly electrofishing survey with simultaneous sampling of water quality and submerged aquatic vegetation (SAV) biomass at 33 locations throughout the Delta. We used generalized linear mixed models to assess the relative influences of water temperature, conductivity, Secchi depth, and SAV biomass density on the abundance of both juvenile‐sized and larger Largemouth Bass. Water temperature had a positive relationship with the abundance of both size‐classes, but only juvenile‐sized fish had a positive association with SAV biomass density, with highest abundances at intermediate SAV densities. In contrast, larger fish were generally ubiquitous across all sampling conditions, even when SAV was absent or present at low densities. Our results on the Largemouth Bass–SAV relationship are consistent with those of previous studies from lake systems within the Largemouth Bass's native range, where they interact with a different SAV species assemblage. These results are supportive of the hypothesis that the proliferation of Brazilian waterweed has expanded Largemouth Bass rearing habitat in the Delta. Finally, this study has implications for tidal wetland restoration plans for the Delta, suggesting that the larger‐sized Largemouth Bass may still inhabit restored areas even if invasive SAV establishment is limited. Received March 30, 2015; accepted October 27, 2015